Cardiac rehabilitation for heart failure can improve quality of life and fitness. (1st October 2019) - Cook, Rob; Davidson, Peter; Martin, Rosie
The study: Taylor RS, Walker S, Ciani O, et al. Exercise-based cardiac rehabilitation for chronic heart failure: the EXTRAMATCH II individual participant data meta-analysis. Health Technol Assess 2019;23:1-98. This project was funded by the NIHR Health Technology Assessment Programme (project number 15/80/30). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000803/cardiac-rehabilitation-for-heart-failure-can-improve-quality-of-life-and-fitness